Production of a bacterial secretome highly efficient for the deconstruction of xylans - Topalian, Juliana (2024)
Bacteria within the Paenibacillus genus are known to secrete a diverse array of enzymes capable of breaking down plant cell wall polysaccharides. We studied the extracellular xylanolytic activity of Paenibacillus xylanivorans and examined the complete range of secreted proteins when grown on carbohydrate-based carbon sources of increasing complexity, including wheat bran, sugar cane straw, beechwood xylan and sucrose, as control. Our data showed that the relative abundances of secreted proteins varied depending on the carbon source used. Extracellular enzymatic extracts from wheat bran (WB) or sugar cane straw (SCR) cultures had the highest xylanolytic activity, coincidently with the largest representation of carbohydrate active enzymes (CAZymes). Scaling-up to a benchtop bioreactor using WB resulted in a significant enhancement in productivity and in the overall volumetric extracellular xylanase activity, that was further concentrated by freezedrying. The enzymatic extract was efficient in the deconstruction of xylans from different sources as well as sugar cane straw pretreated by alkali extrusion (SCRe), resulting in xylobiose and xylose, as primary products. The overall yield of xylose released from SCRe was improved by supplementing the enzymatic extract with a recombinant GH43 β-xylosidase (EcXyl43) and a GH62 α-l-arabinofuranosidase (CsAbf62A), two activities that were under-represented. Overall, we showed that the extracellular enzymatic extract from P. xylanivorans, supplemented with specific enzymatic activities, is an effective approach for targeting xylan within lignocellulosic biomass.